The influence of corporate governance, corporate social responsibility, and information technology investment on the financial performance of Indonesian mining companies - Henny Amylia Riska; Andi Kushermanto; Dian Priatiningsih; Inayah Risqi Alisa (Universitas Pekalongan, 2024)
The purpose of this study is to analyze the influence of corporate governance, corporate social responsibility, and information technology investment on financial performance. Corporate governance in this study is measured by managerial ownership, the audit committee, and the proportion of independent commissioners. The object of this study is the mining companies listed on the Indonesia Stock Exchange for the 2016–2020 period. The data in this study is secondary data that was collected from the company's annual report, including the audited financial statement. The sample for this study was obtained through purposive sampling, as there were 145 observations from the 29 companies for five years that met the criteria. The technical analysis in this study is multiple regression analysis using SPPS software. The results of this study show that managerial ownership has no effect on financial performance, the audit committee has a positive and significant effect on financial performance, the proportion of independent commissioners has a negative and significant effect on financial performance, corporate social responsibility has a negative effect on financial performance, and information technology investment has a negative and significant effect on financial performance. Theoretically, this study contributes to agency theory and stakeholder theory for the discussion of financial performance. Practically, this research can be a consideration for current investors and potential investors to consider the aspect of financial performance, particularly when investing in the mining company.